Implementasi Teknologi Informasi, Job Flexibility dan Kepuasan Kerja terhadap Kinerja Driver Pada Mitra Gojek (Go-Ride) di Kota Bukittinggi - Ai Elis Karlinda; Silvia Sari (Prosiding, 2022)
This study aims to determine the effect of the implementation of information technology, job flexibility and job satisfaction on the performance of drivers at Gojek (go-ride) partners in Bukittinggi City. This study uses secondary data. The sampling technique in this study was using the Slovin formula. The number of samples obtained as many as 90 respondents. The analysis method of this research uses multiple linear regression analysis. From this research, it can be concluded that information technology has a significant positive effect on driver performance, job flexibility has a significant positive effect on driver performance, job satisfaction has a positive and significant effect on driver performance.